A hyperbolic penalty filter method for semi-infinite programming - Pereira, Ana I. (2008)
This paper presents a new reduction-type method for solving semi-infinite programming problems, where the multi-local optimization is carried out with a sequential simulated annealing algorithm, and the finite reduced problem is solved by a penalty technique based on an hyperbolic function. Global convergence is ensured by a line search filter method. Numerical experiments with a set of known problems show that the algorithm is promising.